2019
DOI: 10.1093/abm/kaz046
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stress Beliefs on Daily Affective Stress Responses

Abstract: Background Negative beliefs about the effects of stress have been associated with poorer health and increased mortality. However, evidence on the psychological mechanisms linking stress beliefs to health is scarce, especially regarding real-life stress. Purpose The aim of the current study was to investigate the effects of stress beliefs on affect in the daily stress process in a population prone to health-impairing effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
(105 reference statements)
1
14
0
Order By: Relevance
“…It is widely recognized that psychological and social factors are linked to work-related stress ( Laferton et al, 2019 ), and these factors strongly affect nurses’ health ( Gigli et al, 2020 ) and clinical care quality ( Burton et al, 2020 ), especially during health crises. This large cross-sectional study compared the psychosocial effects of COVID-19 on distress symptoms and self-perceived health among nurses.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that psychological and social factors are linked to work-related stress ( Laferton et al, 2019 ), and these factors strongly affect nurses’ health ( Gigli et al, 2020 ) and clinical care quality ( Burton et al, 2020 ), especially during health crises. This large cross-sectional study compared the psychosocial effects of COVID-19 on distress symptoms and self-perceived health among nurses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, individuals who perceived themselves as less physically active than others had up to a 71% higher mortality risk compared with individuals who believed they were more active than others, even after controlling for actual levels of activity (Zahrt & Crum, 2017). Likewise, Laferton, Fischer, Ebert, Stenzel, & Zimmermann (2020) found that individuals who hold negative beliefs about stress (e.g., believing that stress is uncontrollable) report more negative affect in relation to daily stress.…”
Section: How Beliefs Modulate Perception and Well-beingmentioning
confidence: 93%
“…A stress mindset affects individuals’ stress perception, stress response, and coping style, so it is closely related to individual emotional outcomes [ 5 , 18 , 19 ]. Compared with individuals with the stress-is-debilitating mindset, individuals with the stress-is-enhancing mindset will generally experience more subjective well-being and less stress, anxiety, and depression [ 18 , 20 , 21 ]. A stress mindset could regulate the cognitive and emotional results of stress events, in which the stress-is-enhancing mindset could be used as a protective factor to reduce the adverse effects of stress itself.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%